McDonaldisasi Sistem Zonasi: Studi Fenomenologi Implementasi PPDB SMP di Kabupaten Karanganyar - Tunggawijaya, Windra; Liestyasari, Siany Indria; Budiati, Atik Catur (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The PPDB implementation process must create objective, transparent and accountable characteristics. Zoning system policy is a solution to create an equitable system. The purpose of this study is to determine the implementation of the zoning system PPDB can meet the elements of McDonaldization and irrationality actions that arise as an impact in the perspective of McDonaldization theory. This study used a descriptive qualitative approach with phenomenological type. Data collection techniques include observation, interviews, questionnaires and documentation. The results showed that the implementation of the PPDB SMP zoning system in Karanganyar Regency was able to meet the expectations of various parties by prioritizing efficiency, effectiveness, and practicality. However, there are various impacts in the form of blank spots, technical obstacles and the emergence of fraud.